PROBING GUYANA’S PROVENANCE OF UNDERDEVELOPMENT per Doctrine of Discovery, Degenerated Democracy & Kleptocracy - Baluch, Nazim (Archives of Business Research, 2019)
ABSTRACT The article, while critically examining the provenance of Guyana’s “underdevelopment”, scrutinizes effects of “Doctrine of Discovery”, and construes that “maraud” befittingly describes the purpose of European discovery voyages to Americas and the Caribbean: the “genocides”; “institutionalized-injustice”; “Human Zoos”; and “systematic atrocities” perpetuated by the European monarchies ravaged Americas, Caribbean, and African nations - inflicting irreversible devastation that persists to this day. The British, questing for Guyana’s resources, setup bare infrastructure and institutions to facilitate “looting” while keeping it “underdeveloped” and its population in “abject poverty”. They were, absolutely, not interested in developing Guyana. However, US & UK continue meddling in Guyanese affairs: bankrolling “Democracy Degeneration”; enabling “Kleptocracy” that has been draining Guyana for the last five decades; and, now, drooling over potential oil money. The article recommends that Guyana is ravenous for legitimate, antidotal, “constitutional reforms” guaranteeing a decentralised, pragmatic, governing model that is: participatory; transparent; accountable; responsive; equitable; and inclusive. To abrogate “Colonial Dehumanisation Effects”, Guyana needs to restore the indigenous peoples “Human Dignity”, “Identity” and “Rights”; rid Guyana of the antiquated, repressive colonial institutions; and reform the archaic education system. “Analog Generation” has to let go; 21st century belongs to “netizens-digital generation”, they must fully participate and play a decisive role in Guyana’s politics and development. Guyanese must use technology to “Reinvent Democracy” and ensure that; it is neither “hacked” nor “hijacked”, “Global Democracy” does not undermine “National Democracy”, and “Political Clientelism” is eradicated for good.